ALAMOYNAQ DUWTAR SAZLARÍNÍŃ MUZÍKA ÍRǴAQLARÍ - Asqarova, Z. (ILIM hám JÁMIYET, 2023)
This article presents information about the melodies inherent in the Karakalpak national instrumental music for alamoinak duutar. For example, we are talking about melismas like grace notes, mordent and their various subspecies, but at the same time, methods for their execution on the Alamoynak duwtar are described in detail and competently.